Chemoprophylaxis and Venous Thromboembolism in Traumatic Brain Injury at Different Trauma Centers. Issue 4 (April 2020) - Yeates, Eric O.; Grigorian, Areg; Schubl, Sebastian D.; Kuza, Catherine M.; Joe, Victor; Lekawa, Michael; Borazjani, Boris; Nahmias, Jeffry
Patients with severe traumatic brain injury (TBI) are at an increased risk of venous thromboembolism (VTE). Because of concerns of worsening intracranial hemorrhage, clinicians are hesitant to start VTE chemoprophylaxis in this population. We hypothesized that ACS Level I trauma centers would be more aggressive with VTE chemoprophylaxis in adults with severe TBI than Level II centers. We also predicted that Level I centers would have a lower risk of VTE. We queried the Trauma Quality Improvement Program (2010–2016) database for patients with Abbreviated Injury Scale scores of 4 and 5 of the head and compared them based on treating the hospital trauma level. Of 204, 895 patients with severe TBI, 143, 818 (70.2%) were treated at Level I centers and 61, 077 (29.8%) at Level II centers. The Level I cohort had a higher rate of VTE chemoprophylaxis use (43.2% vs 23.3%, P < 0.001) and a shorter median time to chemoprophylaxis (61.9 vs 85.9 hours, P < 0.001). Although Level I trauma centers started VTE chemoprophylaxis more often and earlier than Level II centers, there was no difference in the risk of VTE ( P = 0.414) after controlling for covariates. Future prospective studies are warranted to evaluate the timing, safety, and efficacy of early VTE chemoprophylaxis in severe TBI patients.